2018
DOI: 10.3892/ol.2018.8481
|View full text |Cite
|
Sign up to set email alerts
|

miR‑371‑5p suppresses the proliferative and migratory capacity of human nasopharyngeal carcinoma by targeting BCL2

Abstract: The aim of the present study was to investigate the expression and function of microRNA (miR)-371-5p in nasopharyngeal carcinoma (NPC). The levels of miR-371-5p were analyzed in nasopharyngeal epithelium tissues, NPC tissues, human NPC cell lines and NP69 cells using reverse transcription-quantitative polymerase chain reaction analysis. The association between the level of miR-371-5p and clinicopathological variables was also investigated. Cell proliferation was determined using an MTT assay, and the activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that the overexpressed miR-371-5p had considerably accelerated the G1/S phase transformation in hepatoma cells and thereby promoted hepatocellular carcinoma growth . In addition, miR-371-5p significantly suppressed the cell proliferation and migration of human nasopharyngeal carcinoma via inhibiting the expression of the antiapoptotic protein BCL-2 . Several lines of inquiries have evidenced that miR-371-5p was notably downregulated in CRC and repressed the cell proliferation, invasion, metastasis, and self-renewal properties of CRC, , while no data currently exist to describe the role of miR-371-5p in cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the overexpressed miR-371-5p had considerably accelerated the G1/S phase transformation in hepatoma cells and thereby promoted hepatocellular carcinoma growth . In addition, miR-371-5p significantly suppressed the cell proliferation and migration of human nasopharyngeal carcinoma via inhibiting the expression of the antiapoptotic protein BCL-2 . Several lines of inquiries have evidenced that miR-371-5p was notably downregulated in CRC and repressed the cell proliferation, invasion, metastasis, and self-renewal properties of CRC, , while no data currently exist to describe the role of miR-371-5p in cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tumor suppressor miRNAs that previously had been shown to take part in modulating the expression of Bcl-2, including miR-16, miR-29c, miR-15a, and miR-184, were assayed simultaneously in GW501516-treated C666-1 cells. Their expression was usually attenuated in NPC cells, and this led to accelerated tumorigenesis of the NPC cells 8,23 . The cell proliferation, migration, and invasion of the NPC cells could be suppressed by forced expression of these miRNAs, which was found to be achieved majorly through targeting apoptotic-associated proteins 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Their expression was usually attenuated in NPC cells, and this led to accelerated tumorigenesis of the NPC cells 8,23 . The cell proliferation, migration, and invasion of the NPC cells could be suppressed by forced expression of these miRNAs, which was found to be achieved majorly through targeting apoptotic-associated proteins 8 . As a tumor suppressor in several kinds of human cancers, miR-16 has been identified to inhibit CNE-2 cell proliferation and invasion, and increase apoptosis and chemo- or radiosensitivity by repressing its downstream target Bcl-2 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA-371-5p is seen as a potential stimulant of anoikis since higher levels of the miRNA correlated with lower levels of Bcl-2. [32] Survivin, an anti-apoptotic protein identified in several cancers to inhibit anoikis, may also be regulated by miRNA-34a. It has been hypothesized that miRNA-34a may downregulate cell proliferation in HNSCC through the inhibition of survivin [33].…”
Section: Mirnas Involved In Pathological Processes Of Metastasis Amentioning
confidence: 99%